Additional workload evaluation of a stereoscopic film production, based on a case study comparison of a classical monoscopic commercial production - Pieniak, Jan
The change of technologies and digital improvement in the film industry has made it possible to apply new media content to film. Digital cinema is providing the audience with a new dimension of film experience. By adding the feature to screen movies in stereoscopic1 mode, the audience is taken into the scenery itself. Nowadays stereoscopic films are a standard at cinemas, but there is a significant change for the filmmaking industry. Stereoscopic films have to be produced also in a stereoscopic way, which affects and restricts the common work of filmmaking people. This work provides the reader with fundamental knowledge about stereoscopy. This work points out the additional workload if a common production will be produced in the stereoscopic way. Thus the reader is able to estimate the extra workload for a stereoscopic production and knows where the daily work will be restricted. 1 Stereoscopic designates the spatial visual cognition of the world surrounding the viewer.